Deep Learning with TensorFlow : Explore neural networks and build intelligent systems with Python, 2nd Edition /: Explore neural networks and build intelligent systems with Python, 2nd Edition. (2018) - Zaccone, Giancarlo; Karim, Md. Rezaul
No abstract available